2000
DOI: 10.4049/jimmunol.164.1.201
|View full text |Cite
|
Sign up to set email alerts
|

Surface Expression of the IFN-γR2 Chain Is Regulated by Intracellular Trafficking in Human T Lymphocytes

Abstract: The surface and cytoplasmic expressions of the transducing chain (IFN-γR2) of the heterodimeric IFN-γ receptor on human T lymphocytes have been investigated. We show that its surface expression is low, whereas high cytoplasmic levels are found in both resting and PHA-activated T lymphocytes. This low expression does not prevent activated T cells from responding to IFN-γ, because it induces IFN-regulatory factor 1 expression. Low surface IFN-γR2 expression appears to be due to recycling between cytoplasmic stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 43 publications
3
50
0
Order By: Relevance
“…We have previously shown that in human T lymphoblasts, internalization of IFN-␥R2 induces at least a 2-fold increase of cell-associated specific fluorescence of anti-IFN-␥R2 mAb uptake after 4-hour incubation at 37°C. 17 In ST4 cells cultured with serum for 24 hours, an about 2-fold increase of cell-associated specific fluorescence of anti-IFN-␥R2 mAb uptake was observed after 4-hour incubation at 37°C ( Figure 3A). In contrast, no anti-IFN-␥R2 mAb uptake was observed on ST4 cells cultured for 24 hours in the absence of serum ( Figure 3A), indicating that IFN-␥R2 internalization was inhibited.…”
Section: Igf-1 Induces Anti-ifn-␥r2 Mab Uptake In Human Malignant T Lmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that in human T lymphoblasts, internalization of IFN-␥R2 induces at least a 2-fold increase of cell-associated specific fluorescence of anti-IFN-␥R2 mAb uptake after 4-hour incubation at 37°C. 17 In ST4 cells cultured with serum for 24 hours, an about 2-fold increase of cell-associated specific fluorescence of anti-IFN-␥R2 mAb uptake was observed after 4-hour incubation at 37°C ( Figure 3A). In contrast, no anti-IFN-␥R2 mAb uptake was observed on ST4 cells cultured for 24 hours in the absence of serum ( Figure 3A), indicating that IFN-␥R2 internalization was inhibited.…”
Section: Igf-1 Induces Anti-ifn-␥r2 Mab Uptake In Human Malignant T Lmentioning
confidence: 99%
“…13 The fact that IFN-␥R2 protein is prevalently accumulated in the cytoplasm of these malignant T-cell lines 13 underlies an IFN-␥-independent IFN-␥R2 internalization mechanism. 17 Since these T-cell lines express high surface levels of IGF-1R and do not secrete IGF-1 (Schillaci et al 28 and data not shown), we evaluated the effect of IGF-1 (100 ng/mL) on IFN-␥R2 internalization when they were cultured in the absence of serum. Since insulin, which is also present in serum, 29 activates IGF-1R, although at 10-fold higher concentration than IGF-1, 30 a 36-fold higher concentration of insulin was used to assess the specificity of action of IGF-1 on IFN-␥R2 expression.…”
Section: Igf-1 Induces Internalization Of Ifn-␥r2 Chain In Human T Lymentioning
confidence: 99%
See 3 more Smart Citations